Importance Evaluation of Power Grid Nodes Based on Complex Network Theory - TAN Yanghong, ZHANG Jing, LI Xiao (Ji suan ji gong cheng, 2019)
The important nodes in the power grid have an important impact on the safe and orderly operation of the power grid.If these nodes fail,it will cause a large area of the power grid.Traditional methods of assessing the importance of grid nodes often ignore the influence of decision makers' experience and knowledge on the results of the assessment.Therefore,the prospect theory is introduced and an improved Technique for Order Preference by Similarity to Ideal Solution(TOPSIS)method is proposed.The introduction of relative entropy solves the problem that the traditional TOPSIS method can not distinguish the vertical line nodes in the positive and negative ideal solutions,and uses the gray correlation degree to measure the Euclidean distance and the edge coupling degree of the curve,so that the evaluation result is more accurate.Taking the IEEE 39 node system as an example,the analysis results show that the method can effectively identify important nodes and the node recognition is high.